Evaluation of surface tensions and root-dentin surface contact angles of different endodontic irrigation solutions - Hatice Buyukozer Ozkan; Arslan Terlemez; Ahmet Burcin Batibay; Hilal Erdogan; Funda Kont Cobankara (BMC, 2024)
Abstract Background Surface tension and contact angle properties, which play a crucial role in determining the effectiveness of irrigation solutions in penetrating dentin surfaces and dentin tubules, are highly important for the development of new irrigation solutions and their preferences. The aim of the current study was to compare the surface tension and contact angle properties of different irrigation solutions used in endodontics, both on the dentin surface and within dentin tubules. Methods In this study, the contact angles and surface tensions of 5.25% sodium hypochlorite (NaOCl), 17% ethylenediaminetetraacetic acid (EDTA), 2% chlorhexidine (CHX), 5% boric acid (BA), 0.02% hypochlorous acid (HOCl), 0.2% chlorine dioxide (ClO2), Biopure MTAD, QMix solutions, and distilled water (control group) were measured. Measurements were conducted using a goniometer device (Attension Theta Lite Tensiometer, Biolin Scientific, USA), employing the sessile drop method for contact angle measurements on pre-prepared dentin surfaces, and the pendant drop method for surface tension. Results Contact angle measurements revealed no statistically significant differences between the contact angle values of MTAD, ClO2, and CHX or between NaOCl, QMix, BA, and HOCl (p > 0.05). However, EDTA exhibited a significantly greater contact angle than did MTAD, ClO2, CHX, NaOCl, QMix, BA, and HOCl (p < 0.05). Furthermore, the contact angle of dentin with distilled water was greater than that with all other solutions tested (p < 0.05). Surface tension measurements revealed that the surface tension values of QMix and MTAD were statistically similar (p > 0.05). CHX exhibited lower surface tension than distilled water and HOCl (p < 0.05), and it also had lower surface tension than ClO2, NaOCl, and BA (p < 0.05). Additionally, the surface tension of the samples treated with EDTA was greater than that of all other solutions tested (p < 0.05). Conclusion The direct linear relationship between the surface tension of liquids and contact angles on different surfaces may not always hold true, and these values should be considered independently for each solution on various surfaces. Considering the contact angles and surface tension properties of irrigation solutions with root canal dentin, it can be suggested for clinical use that ClO2 could be recommended over NaOCl, and similarly, BA could be recommended over EDTA.